Stem Cell-Derived Human Striatal Progenitors Innervate Striatal Targets and Alleviate Sensorimotor Deficit in a Rat Model of Huntington Disease - Besusso, Dario (Stem Cell Reports, 2020)
Huntington disease (HD) is an inherited late-onset neurological disorder characterized by progressive neuronal loss and disruption of cortical and basal ganglia circuits. Cell replacement using human embryonic stem cells may offer the opportunity to repair the damaged circuits and significantly ameliorate disease conditions. Here, we showed that in-vitro-differentiated human striatal progenitors undergo maturation and integrate into host circuits upon intra-striatal transplantation in a rat model of HD. By combining graft-specific immunohistochemistry, rabies virus-mediated synaptic tracing, and ex vivo electrophysiology, we showed that grafts can extend projections to the appropriate target structures, including the globus pallidus, the subthalamic nucleus, and the substantia nigra, and receive synaptic contact from both host and graft cells with 6.6 ± 1.6 inputs cell per transplanted neuron. We have also shown that transplants elicited a significant improvement in sensory-motor tasks up to 2 months post-transplant further supporting the therapeutic potential of this approach.